Investigation of passive bearing for biomedical application - Cao, Qian (2010)
Hydrodynamic bearings have been around for many years and are widely used in many industries. The principle of the hydrodynamic bearing is that fluid is pumped onto the inner surface of the bearing, forming a lubricating wedge around or under the shaft. The simplicity concept and low cost of production and maintenance makes the hydrodynamic bearings popular with design engineers. In today modern technology, hydrodynamic bearings are also used in the biomedical and bioengineering industries.